Penyuluhan Agama Kristen Kepada Pemuda-Pemudi Gereja HKBP Pagar Beringin Kecamatan Sipoholon Kabupaten Tapanuli Utara - Mutiara Agustina Aritonang; Ester Claudya Sitinjak; Luica C. Naibaho; Ayu Andira Sihotang; Vetran Yusuf Tarihoran; Melina Agustina Sipahutar (Journal of Innovative and Creativity, 2025)
Christian Religious Counseling for young men and women of the HKBP Pagar Beringin Church, Sipoholon District, North Tapanuli Regency, faces challenges in the digital era such as secularism, the influence of social media, and a crisis of faith identity among Naposobulung (aged 18-35 years unmarried), who are vulnerable to losing their passion for church service. This study uses a qualitative descriptive phenomenological approach with semi-structured in-depth interviews, participant observation during bimluh and services, and document analysis such as the Guidance Guidance Manuscript (BP) and the 2024 HKBP Naposobulung Guidebook for 25-30 informants from Ministry of Religious Affairs counselors, young men and women, and congregation councils. The results show that effective counseling through interactive methods (thematic Bible studies, group discussions, digital media) increases spiritual growth, service participation, and resilience to digital ethics issues and promiscuity, despite being hampered by cross-sectoral coordination and digital literacy of counselors. The synergy between IAKN Tarutung and the church has resulted in holistic empowerment, strengthening the regeneration of the church's three tasks (kerygma, leitourgia, diakonia).